2018
DOI: 10.1371/journal.pone.0194800
|View full text |Cite
|
Sign up to set email alerts
|

The deferred embryo transfer strategy improves cumulative pregnancy rates in endometriosis-related infertility: A retrospective matched cohort study

Abstract: BackgroundControlled ovarian stimulation in assisted reproduction technology (ART) may alters endometrial receptivity by an advancement of endometrial development. Recently, technical improvements in vitrification make deferred frozen-thawed embryo transfer (Def-ET) a feasible alternative to fresh embryo transfer (ET). In endometriosis-related infertility the eutopic endometrium is abnormal and its functional alterations are seen as likely to alter the quality of endometrial receptivity. One question in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 54 publications
2
36
0
1
Order By: Relevance
“…Women in the control group had more often a fresh ET strategy than in the OMA group (p<0.001), but the type of transfer did not impact the ovarian response to stimulation (p = 0.981). In line with current scientific knowledge, the deferred ET strategy may increase pregnancy chances in endometriosis-affected women population [ 37 ]. However, the absence of randomized controlled studies in this population and the absence of superiority of this strategy in non-endometriosis women does not allow to differentiate between deferred ET and a fresh ET strategies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 71%
“…Women in the control group had more often a fresh ET strategy than in the OMA group (p<0.001), but the type of transfer did not impact the ovarian response to stimulation (p = 0.981). In line with current scientific knowledge, the deferred ET strategy may increase pregnancy chances in endometriosis-affected women population [ 37 ]. However, the absence of randomized controlled studies in this population and the absence of superiority of this strategy in non-endometriosis women does not allow to differentiate between deferred ET and a fresh ET strategies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 71%
“…In terms of ongoing pregnancy rate we found a similarly reduction of ongoing pregnancy rate in the endometriosis group compared to the control one in the freeze all cycles, consequently we cannot conclude that endometriosis women have better ART outcome after freeze all cycle. This data is supported by the recent study of Roque and colleagues [19], that reported that even if initial studies showed that the freeze-all strategy could be beneficial for certain groups of infertility including endometriosis patients [20], there is still lack of evidence to support its routine use not only for indications as endometriosis but also for implantation failure. In conclusion the data published until now is very controversial about better ART outcomes after freeze all cycles in endometriosis patients [19].…”
Section: Discussionmentioning
confidence: 78%
“… 1995 to 2015. GDM,hyper, Preterm, Very preterm, Belva 2008 [ 18 ] All pregnancies after transfer of FET No statement 6402/1351 Unmatched cohort study No statement MR, MPR, LBR, OPR, PR, EPR, LBW, Stil Bourdon 2018 [ 19 ] Women with endometriosis infertile 34.3 ± 3.9/34.3 ± 4.1 135/135 Retrospective matched cohort study Oct 2012 to Dec 2014 LBR, MPR, OPR Cavoretto2020 [ 20 ] Women undergoing fresh ET or FET 35.9 ± 3.9/34.9 ± 5.1 164 / 203 Prospective longitudinal study Jan 2016 to Dec 2018 GDM, PTD, PE, SGA, LGA Chen 2016 [ 21 ] Infertile women with PCOS 28.2 ± 3.1/28.1 ± 3.0 762/746 Retrospective matched cohort study Jun 2013 to May 2015 CPR, MR, LBR, OPR, PR, OHSS, PTD, PIH, Stil Coates 2017 [ 22 ] Patients undergoing IVF treatment using preimplantation genetic screening 36.6 (25–42)/ 36.7 (27–42) 88/91 RCT Dec 2013 to Aug 2015 IR, MPR, LBR, OPR Eum 2016 [ 23 ] Women who underwent one or two fresh ET or FET Using a cutoff of 35 years 69/206 Retrospective study Jan 2013 to Dec 2014. IR, CPR, MR, LBR, MPR Fauque 2010 [ 24 ] Women with adequate ovarian function < 36 years No statement Prospective NRCT 2005 to 2007 CPR, MR, LBR, MPR, EPR.…”
Section: Resultsmentioning
confidence: 99%